2014
DOI: 10.4278/ajhp.120711-quan-339
|View full text |Cite
|
Sign up to set email alerts
|

Association of Street Connectivity and Road Traffic Speed with Park Usage and Park-Based Physical Activity

Abstract: In addition to park proximity and the design of park features, ensuring direct and safe access to parks through street network design and traffic speed reduction strategies may be key to facilitating park-related physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 40 publications
3
57
2
Order By: Relevance
“…For example, we found no association (cross-sectional or longitudinal) between availability of sidewalks and ORA use or rating of quality of street lighting and ORA use. At the same time, ratings of lighter motorized traffic were marginally related to increased ORA use, which is consistent with past research about neighborhood traffic speed and park visitation among adults (Kaczynski et al, 2014a). However, rating one’s neighborhood as a pleasant place to walk was related to decreased ORA use over time, which may simply represent a displacement of PA from parks and trails to other neighborhood settings (e.g., sidewalks, streets).…”
Section: Discussionsupporting
confidence: 90%
“…For example, we found no association (cross-sectional or longitudinal) between availability of sidewalks and ORA use or rating of quality of street lighting and ORA use. At the same time, ratings of lighter motorized traffic were marginally related to increased ORA use, which is consistent with past research about neighborhood traffic speed and park visitation among adults (Kaczynski et al, 2014a). However, rating one’s neighborhood as a pleasant place to walk was related to decreased ORA use over time, which may simply represent a displacement of PA from parks and trails to other neighborhood settings (e.g., sidewalks, streets).…”
Section: Discussionsupporting
confidence: 90%
“…A study of parks in New York City noted that although there may be more parks in lower income neighborhoods, there was lower social access because of higher crime, fewer park acres, and more noxious land uses (Weiss et al, 2011). Other contextual factors also influence park use including street connectivity (Kaczynski, Koohsari, Stanis, Bergstrom, & Sugiyama, 2014) and land use mix (Frank et al, 2012). While one study indicated no difference in perceived accessibility to parks among different racial/ethnic groups (Carlson, Brooks, Brown, & Buchner, 2010), others have shown distinct differences in perceptions of park safety, with minority groups, including African Americans and Latinos, perceiving local parks as less safe (Boslaugh, Luke, Brownson, Naleid, & Kreuter, 2004; Tappe, Glanz, Sallis, Zhou, & Saelens, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…, they may also have their own distinct influences on public open space-related physical activity. For example, Kaczynski et al (2014) found that regulating lower traffic speeds on streets surrounding public open space encourages public open space usage. Another study found perceived safety from crime, traffic and aesthetics in the surrounding neighbourhood was associated with greater public open spacerelated walking (Koohsari et al, 2013c).…”
Section: Quality Of Public Open Spacementioning
confidence: 98%